2023
DOI: 10.1051/e3sconf/202340103038
|View full text |Cite
|
Sign up to set email alerts
|

Methods of new technological developments of electric motors based on soft magnetic materials

U. T. Berdiev,
I. K. Kolesnikov,
M. N. Tuychieva
et al.

Abstract: Application conditions of composite materials based on ASC100.29 iron powders with an oxide coating in electrical machine devices as a stator with improved performance are considered in the article. The conditions for increasing the stability of the operation of electric motors are determined based on changes in the thickness of the oxide layer. Three-dimensional models of magnetic circuits were used, which made it possible to achieve a force of up to 4500 N with a torque of 3 to 8 Nm, which made it possible t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…The study of losses during magnetization reversal of samples of magnetic circuits showed that hysteresis losses are 25-30% higher for samples based on powders sprayed with air compared to losses for magnetic circuits based on powders sprayed with water (Figure 4) [7,9]. On the whole, comparative studies have shown a certain advantage in the value of magnetization reversal losses of purer iron powders obtained by the water spray method in comparison with powders sprayed with air [3,5,8]. The main parameter that determines the possibility of using products in electrical devices is the magnitude of electromagnetic losses at different frequencies [5,[8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Research Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The study of losses during magnetization reversal of samples of magnetic circuits showed that hysteresis losses are 25-30% higher for samples based on powders sprayed with air compared to losses for magnetic circuits based on powders sprayed with water (Figure 4) [7,9]. On the whole, comparative studies have shown a certain advantage in the value of magnetization reversal losses of purer iron powders obtained by the water spray method in comparison with powders sprayed with air [3,5,8]. The main parameter that determines the possibility of using products in electrical devices is the magnitude of electromagnetic losses at different frequencies [5,[8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Research Resultsmentioning
confidence: 99%
“…On the whole, comparative studies have shown a certain advantage in the value of magnetization reversal losses of purer iron powders obtained by the water spray method in comparison with powders sprayed with air [3,5,8]. The main parameter that determines the possibility of using products in electrical devices is the magnitude of electromagnetic losses at different frequencies [5,[8][9][10][11][12][13][14][15][16][17][18][19][20]. The results of preliminary studies of losses from the magnitude of induction are shown in Figure 5.…”
Section: Research Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is proposed to use the Chinese wind generator Axies Wind SR -600/800 as a wind turbine. The efficiency of such wind generators is very high [14][15][16][17][18][19][20].…”
Section: Fig3 Average Wind Speed Throughout the Year Inmentioning
confidence: 99%